Engineering preparation and engineering protection of urban areas in the context of modern digital solutions - CHERTKOV, Oleg (Ways to Improve Construction Efficiency, 2025)
In the context of the rapid development of modern urban areas and the increasing anthropogenic and climatic load, the study of the features of engineering preparation and engineering protection of urban territories through the implementation of modern digital solutions is highly relevant. These processes are crucial for ensuring the sustainable development of cities and enhancing the level of safety, functionality, and comfort of the population's life. Engineering preparation includes a set of measures to create favourable conditions for development (terrain planning, drainage, utility installation), while engineering protection is aimed at preventing the negative impact of natural (landslides, flooding, erosion) and man-made processes. The implementation of digital technologies actively optimizes planning, design, and management processes of urban systems, ensuring their transparency, coherence, and resource efficiency. Geographic Information Systems (GIS) enable highly accurate spatial analysis of engineering-geological conditions and risks; BIM modeling improves the quality of design solutions for engineering structures; and IoT sensors and automated monitoring of utility networks, soil conditions, and natural processes provide real-time data collection. The integration of these tools into the Digital Twin concept allows for increased accuracy of engineering calculations, conducting hydrodynamic and geotechnical modeling, promptly identifying potential risks, and making well-founded management decisions, thereby reducing the probability of accidents and disasters. The integration of digital platforms into the risk management system creates a unified information data space, significantly enhancing the adaptability of urban areas to climate change, man-made threats, and intensive construction. The research emphasizes that the effective application of digital technologies in the field of engineering preparation and protection is a key factor in forming the "smart" and resilient cities of the future (Smart City). The article analyzes the main stages of engineering preparation and directions of territory protection, illustrates their improvement through digital tools, and provides practical examples of using GIS integration in planning water protection zones (Kyiv) and a digital monitoring system for landslide-prone areas (Lviv). The results demonstrate that digital solutions allow for a transition from reactive to predictive risk management.